5.1.73 Problems 7201 to 7300

Table 5.145: First order ode

#

ODE

Mathematica

Maple

16169

\[ {}\sin \left (y\right )-y \cos \left (t \right )+\left (t \cos \left (y\right )-\sin \left (t \right )\right ) y^{\prime } = 0 \]

16170

\[ {}y^{2}+\left (2 t y-2 \cos \left (y\right ) \sin \left (y\right )\right ) y^{\prime } = 0 \]

16171

\[ {}\frac {y}{t}+\ln \left (y\right )+\left (\frac {t}{y}+\ln \left (t \right )\right ) y^{\prime } = 0 \]

16172

\[ {}y^{\prime } = y^{2}-x \]

16173

\[ {}y^{\prime } = \sqrt {x -y} \]

16174

\[ {}y^{\prime } = t y^{3} \]

16175

\[ {}y^{\prime } = \frac {t}{y^{3}} \]

16176

\[ {}y^{\prime } = -\frac {y}{t -2} \]

16300

\[ {}y^{\prime }-4 y = t^{2} \]

16301

\[ {}y^{\prime }+y = \cos \left (2 t \right ) \]

16302

\[ {}y^{\prime }-y = {\mathrm e}^{4 t} \]

16303

\[ {}y^{\prime }+4 y = {\mathrm e}^{-4 t} \]

16304

\[ {}y^{\prime }+4 y = t \,{\mathrm e}^{-4 t} \]

16664

\[ {}y^{\prime } = x^{2}+y^{2} \]

16665

\[ {}y^{\prime } = \frac {x}{y} \]

16666

\[ {}y^{\prime } = y+3 y^{{1}/{3}} \]

16667

\[ {}y^{\prime } = \sqrt {x -y} \]

16668

\[ {}y^{\prime } = \sqrt {x^{2}-y}-x \]

16669

\[ {}y^{\prime } = \sqrt {1-y^{2}} \]

16670

\[ {}y^{\prime } = \frac {1+y}{x -y} \]

16671

\[ {}y^{\prime } = \sin \left (y\right )-\cos \left (x \right ) \]

16672

\[ {}y^{\prime } = 1-\cot \left (y\right ) \]

16673

\[ {}y^{\prime } = \left (3 x -y\right )^{{1}/{3}}-1 \]

16674

\[ {}y^{\prime } = \sin \left (x y\right ) \]

16675

\[ {}x y^{\prime }+y = \cos \left (x \right ) \]

16676

\[ {}y^{\prime }+2 y = {\mathrm e}^{x} \]

16677

\[ {}\left (-x^{2}+1\right ) y^{\prime }+x y = 2 x \]

16678

\[ {}y^{\prime } = 1+x \]

16679

\[ {}y^{\prime } = x +y \]

16680

\[ {}y^{\prime } = y-x \]

16681

\[ {}y^{\prime } = \frac {x}{2}-y+\frac {3}{2} \]

16682

\[ {}y^{\prime } = \left (y-1\right )^{2} \]

16683

\[ {}y^{\prime } = \left (y-1\right ) x \]

16684

\[ {}y^{\prime } = x^{2}-y^{2} \]

16685

\[ {}y^{\prime } = \cos \left (x -y\right ) \]

16686

\[ {}y^{\prime } = y-x^{2} \]

16687

\[ {}y^{\prime } = x^{2}+2 x -y \]

16688

\[ {}y^{\prime } = \frac {1+y}{x -1} \]

16689

\[ {}y^{\prime } = \frac {x +y}{x -y} \]

16690

\[ {}y^{\prime } = 1-x \]

16691

\[ {}y^{\prime } = 2 x -y \]

16692

\[ {}y^{\prime } = x^{2}+y \]

16693

\[ {}y^{\prime } = -\frac {y}{x} \]

16694

\[ {}y^{\prime } = 1 \]

16695

\[ {}y^{\prime } = \frac {1}{x} \]

16696

\[ {}y^{\prime } = y \]

16697

\[ {}y^{\prime } = y^{2} \]

16698

\[ {}y^{\prime } = x^{2}-y^{2} \]

16699

\[ {}y^{\prime } = y^{2}+x \]

16700

\[ {}y^{\prime } = x +y \]

16701

\[ {}y^{\prime } = 2 y-2 x^{2}-3 \]

16702

\[ {}x y^{\prime } = 2 x -y \]

16703

\[ {}1+y^{2}+\left (x^{2}+1\right ) y^{\prime } = 0 \]

16704

\[ {}1+y^{2}+x y y^{\prime } = 0 \]

16705

\[ {}\sin \left (x \right ) y^{\prime }-y \cos \left (x \right ) = 0 \]

16706

\[ {}1+y^{2} = x y^{\prime } \]

16707

\[ {}x \sqrt {1+y^{2}}+y y^{\prime } \sqrt {x^{2}+1} = 0 \]

16708

\[ {}x \sqrt {1-y^{2}}+y \sqrt {-x^{2}+1}\, y^{\prime } = 0 \]

16709

\[ {}{\mathrm e}^{-y} y^{\prime } = 1 \]

16710

\[ {}y \ln \left (y\right )+x y^{\prime } = 1 \]

16711

\[ {}y^{\prime } = a^{x +y} \]

16712

\[ {}{\mathrm e}^{y} \left (x^{2}+1\right ) y^{\prime }-2 x \left (1+{\mathrm e}^{y}\right ) = 0 \]

16713

\[ {}2 x \sqrt {1-y^{2}} = \left (x^{2}+1\right ) y^{\prime } \]

16714

\[ {}{\mathrm e}^{x} \sin \left (y\right )^{3}+\left (1+{\mathrm e}^{2 x}\right ) \cos \left (y\right ) y^{\prime } = 0 \]

16715

\[ {}y^{2} \sin \left (x \right )+\cos \left (x \right )^{2} \ln \left (y\right ) y^{\prime } = 0 \]

16716

\[ {}y^{\prime } = \sin \left (x -y\right ) \]

16717

\[ {}y^{\prime } = a x +b y+c \]

16718

\[ {}\left (x +y\right )^{2} y^{\prime } = a^{2} \]

16719

\[ {}x y^{\prime }+y = a \left (x y+1\right ) \]

16720

\[ {}a^{2}+y^{2}+2 x \sqrt {a x -x^{2}}\, y^{\prime } = 0 \]

16721

\[ {}y^{\prime } = \frac {y}{x} \]

16722

\[ {}\cos \left (y^{\prime }\right ) = 0 \]

16723

\[ {}{\mathrm e}^{y^{\prime }} = 1 \]

16724

\[ {}\sin \left (y^{\prime }\right ) = x \]

16725

\[ {}\ln \left (y^{\prime }\right ) = x \]

16726

\[ {}\tan \left (y^{\prime }\right ) = 0 \]

16727

\[ {}{\mathrm e}^{y^{\prime }} = x \]

16728

\[ {}\tan \left (y^{\prime }\right ) = x \]

16729

\[ {}x^{2} y^{\prime } \cos \left (y\right )+1 = 0 \]

16730

\[ {}x^{2} y^{\prime }+\cos \left (2 y\right ) = 1 \]

16731

\[ {}x^{3} y^{\prime }-\sin \left (y\right ) = 1 \]

16732

\[ {}\left (x^{2}+1\right ) y^{\prime }-\frac {\cos \left (2 y\right )^{2}}{2} = 0 \]

16733

\[ {}{\mathrm e}^{y} = {\mathrm e}^{4 y} y^{\prime }+1 \]

16734

\[ {}\left (1+x \right ) y^{\prime } = y-1 \]

16735

\[ {}y^{\prime } = 2 x \left (\pi +y\right ) \]

16736

\[ {}x^{2} y^{\prime }+\sin \left (2 y\right ) = 1 \]

16737

\[ {}x y^{\prime } = y+x \cos \left (\frac {y}{x}\right )^{2} \]

16738

\[ {}x -y+x y^{\prime } = 0 \]

16739

\[ {}x y^{\prime } = y \left (\ln \left (y\right )-\ln \left (x \right )\right ) \]

16740

\[ {}x^{2} y^{\prime } = y^{2}-x y+x^{2} \]

16741

\[ {}x y^{\prime } = y+\sqrt {y^{2}-x^{2}} \]

16742

\[ {}2 x^{2} y^{\prime } = x^{2}+y^{2} \]

16743

\[ {}4 x -3 y+\left (2 y-3 x \right ) y^{\prime } = 0 \]

16744

\[ {}y-x +\left (x +y\right ) y^{\prime } = 0 \]

16745

\[ {}x +y-2+\left (1-x \right ) y^{\prime } = 0 \]

16746

\[ {}3 y-7 x +7-\left (3 x -7 y-3\right ) y^{\prime } = 0 \]

16747

\[ {}x +y-2+\left (x -y+4\right ) y^{\prime } = 0 \]

16748

\[ {}x +y+\left (x -y-2\right ) y^{\prime } = 0 \]

16749

\[ {}2 x +3 y-5+\left (3 x +2 y-5\right ) y^{\prime } = 0 \]

16750

\[ {}8 x +4 y+1+\left (4 x +2 y+1\right ) y^{\prime } = 0 \]